Analysis Legalitas Akta Surat Kuasa Membebankan Hak Tanggungan (SKMHT) Yang Dibuat Dihadapan Notaris dan Pengaruhnya Terhadap Perlindungan Bagi Kreditor - Arina Ratna Paramita; Djumadi Purwoatmodjo (Magister Kenotariatan Universitas Diponegoro, 2022)
AbstractSKMHT is the granting of power in accordance with the understanding of power, namely to carry out or carry out a certain business, in this case, namely